The accuracy of the literacy theory claims in the context of the medieval Arab-Muslim culture. Development of qadiship as an implication of the dissemination of writing and literacy - Prochwicz-Studnicka, Bożena (Reti Medievali Rivista, 2020)
The article is devoted to the application of the literacy theory in the historical studies. The key issue is to verify the accuracy of the literacy theorists’ claims with reference to the medieval Arab-Muslim culture. The point of reference is the development of the judgeship (qadiship). Basing on the analysis of this process the article traces the schemes of transformations which occur – according to the literacy theorists – in the context of the institutional dimension of culture under the influence of writing. The application of the theoretical model of the mutual relations of orality and literacy to the specific socio-cultural reality (i.e. from the first years of Islam to the middle of the ninth century, when the qadiship reached its maturity structurally and functionally) allows to track out “the logic of writing”. The identity of the judgeship was constructed on the basis of a perception of the world formed by the literate communicative order. In other words, the development of the office itself was attained as a result of the gradual textualisation of culture, including the legal culture and the law itself. However, co-occurrence of orality, determined by the manuscript character of the medieval Arab-Muslim culture as well as the dominant world-view factors causing specific values to penetrate into social practice, made the potential for change (carried by writing) manifest itself in a limited extent in the very operation of the institution of qadi.